Analisis Penanganan Polip Nasal di RSUD Labuang Baji: Analysis of Nasal Polyp Treatment at Labuang Baji Regional Hospital - Alfrida, Alfrida (Barongko: Jurnal Ilmu Kesehatan, 2024)
Nasal polyps are a chronic inflammatory disease of the mucous membranes of the nose and paranasal sinuses. The shape of the polyp can be round or oval with a smooth surface and a translucent color like jelly. Even though these nasal polyps have been discovered for a long time, until now the causal factors and pathogenesis are not known for certain. Several factors that are thought to play a role include allergies, chronic inflammation, vasomotor imbalance, and changes in polysaccharides. In this research the researcher used a descriptive research strategy. Namely research that attempts to describe phenomena that occur realistically, real and contemporary. The results of the research show that polyps can appear in both male and female sufferers, from children to old age. If there are polyps in children under 2 years of age, the possibility of meningocele or meningoencephalocele must be ruled out. Epidemiological studies show that the ratio of men to women is 2-3: 1 with a prevalence of 0.2%-4.3%.